The effect of mobile application-based rehabilitation in patients with total knee arthroplasty: A systematic review and meta-analysis - SARI, ZÜBEYİR (My University, 2023)
Objective: Mobile applications have been used frequently in post-operative orthopedic rehabilitation in recent years. However, no systematic review has emphasized the importance of mobile applications in the rehabilitation process after total knee arthroplasty (TKA). This systematic review and meta-analysis aimed to evaluate the effectiveness of mobile application-based rehabilitation practices in patients with TKA. Material and Methods: PubMed, Web-of-Science, Scopus, ScienceDirect and Cochrane databases were searched. The Physiotherapy Evidence Database (PEDro) and the Revised Cochrane risk-of-bias tool randomized trials 2 (RoB2) tools were used to demonstrate the methodological quality and risk of bias. Results: A total of 584 articles were screened. Finally, six papers were included in the systematic review. PEDro scores ranged from 4 to 7 (median: 5.5), indicating fair to good methodological quality. All studies were classified as \"some concerns\" in RoB2. Mobile application-based rehabilitation demonstrated better scores on pain, range of motion (ROM), objective and subjective function, satisfaction and compliance in general. Meta-analysis proved that mobile application-based telerehabilitation demonstrated better results on subjective function (ES:0.57, 95% CI: 0.11–1.02). Conclusion: Compared to conventional rehabilitation, application-based telerehabilitation provides more effective results in function, pain and ROM. Furthermore, mobile application-based rehabilitation should also be considered regarding patient satisfaction and compliance.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Geriatri; Sosyal ve Beşeri Bilimler; Sosyoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Geriatrics; Social Sciences and Humanities; Sociology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Sosyal Bilimler (SOC); Klinik Tıp; Sosyal Bilimler Genel; GERONTOLOJİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; GERİATRİ ve GERONTOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); Social Sciences (SOC); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; SOCIAL SCIENCES, GENERAL; GERONTOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; GERIATRICS & GERONTOLOGY; Sağlık (sosyal bilimler); Sosyal Bilimler ve Beşeri Bilimler; Yaşlanma; Gerontoloji; Geriatri ve Gerontoloji; Health (social science); Social Sciences & Humanities; Aging; Gerontology; Geriatrics and Gerontology; Application; Knee prosthesis; Knee replacement; Smart phone; Telerehabilitation